We need to talk about ‘bad’ resilience - Stephanie M Topp; Dell D Saulnier (BMJ Global Health)
In this analysis, we argue against seeing health system resilience as an inherently positive concept. The rise in the popularity of health system resilience has led to its increasingly normative framing. We question this widely accepted perspective by examining the underlying assumptions associated with this normative framing of ‘good’ resilience. Our focus is on the risks of accepting the assumption, which can lead us to ignore the social nature of health systems and overlook the consequences of change if resilience is seen as a positive, achievable objective. Finally, we suggest that seeing resilience as a normative concept can be detrimental to health system policy and research, and encourage a critical rethinking of these assumptions so that we can maintain resilience’s usefulness for health systems.